Economic Zones as a Factor of Increased Economic Competitiveness of the Region - Bogoviz, Aleksei V.; Ragulina, Yulia V.; Kutukova, Elena S. (International Journal of Economics and Financial Issues, 2016)
One of the most promising and effective ways to raise state and foreign investment holdings for further development of economic potential and opportunities of the region, promoting innovative development and transformation of the region, its economic system there can be formation and development of special economic zones (SEZ). This dynamics of economic zones assumes their further development in the structure of the region as a center of industrial and innovative cluster development which operation is a driving force promoting the domestic economic system on the way of its modernization and advance. Each economy of the region possesses specific peculiarities of available resource and potential development, and also conducts its own policy of development of innovative enterprises, companies and other organizations. All inherent distinctive features and potentials of economic development of the region allow to qualify this or that region as the most competitive one. The paper considers special economic zones of regions of the Russian Federation, their development in the modern conditions of world fluctuations. It reveals the main problems in the field of realization and introduction of SEZ, and the ways of their elimination. The paper also describes priorities for of economic zone realization efficiency their further development both in economy of the region, being a factor of increased competitive advantages, and in the whole state. Keywords: region, special economic zone, innovation, cluster, competitiveness JEL Classifications: O30, O40, G29